Magnetic Somnambulism in Context. Hegel’s Criticism of Kluge on Hypnosis - Andrés Ortigosa Peña (Problemos)
This paper aims to explore Hegel’s conception of hypnosis, which he considers a pathological state. Much of the literature on Hegel’s views on hypnosis suggests that his conception is influenced by the Marquis de Puységur, the discoverer of this phenomenon. However, this paper explores the possibility that Hegel’s conception of hypnosis originates from the mesmerist Kluge. To show this, we analyse Hegel’s critique of hypnosis, which aligns more closely with Kluge’s proposal on hypnosis than that of Marquis de Puységur.